Detection and purification of protein hirudin from local leech using a gel filtration chromatography - Zulhisyam Abdul Kari @ Abdullah; Ahmad Anwar Mohamed Ismail; Ibrahim Che Omar (Universiti Malaysia Kelantan, 2012)
It has long been known that local leech contain a substance with anticoagulant properties. In 1984, the blood-thinning agent (anticoagulant) hirudin was isolated for the first time from leech salivary glands (Weinnberg, 1994). The purification of hirudin, protein profiling and protein quantification from different part of leech are reported. The result shows the sample from leech head was gave the highest result in protein concentration with value of 69.33 µg/ml compared with the sample from the whole body and leech body which was 36.67 µg/ml and 26.67 µg/ml, respectively. Sample from leech head was used for purification by gel permeation chromatography on Sephadex G-75. Fractions which contain significant amounts of protein with absorbance value more than 0.2 at 595 nm were tested on their anti-coagulant activity. The result shows that that the peak number 3 (Number of fraction= 23, optical density (O.D) = 0.256, protein concentration = 82.00 µg/ml) gave the longest time of blood to clot (123.33±15.28 minutes) and the clotted blood was not contracted up to 380.00±17.32 minutes compared with peak number 2 (Number of fraction= 21, optical density (O.D) = 0.293, protein concentration = 94.33 µg/ml) and 5 (Number of fraction= 36, optical density (O.D) = 0.214, protein concentration = 68.00 µg/ml ) where the blood was clot in 13.33±2.89 and 23.33±2.89 minutes and the clotted blood was not contracted up to 24.33±0.58 and 41.67±2.89 minutes, respectively. Crude protein and eluted fractions which contain significant amounts of protein with the longest time of blood to clot were subjected to SDS-PAGE analysis. The result shows that the molecular weight of protein hirudin was about 11.36 kDa. From the purification by Sephadex G-75 Gel Filtration profiles of leech crude extract from different parts of body indicates that anti-coagulant agent (protein hirudin) was only exist in leech head (salivary glands).